Testing the Relationship of Employee Empowerment and Organisational Performance - Badjie, Gibriel; Thoyib, Armanu; Hadiwidjojo, Djumilah; Rofiq, Ainur (Universitas Muhammadiyah Magelang, 2020)
The research aimed to test the new measures of employee empowerment in a collectively social oriented society. The study applied questionnaire-based survey to obtain data and test the relationship between employee empowerment and organisational performance. A total of 80 completed questionnaires from the senior HR personnel from 40 organisations in the Gambia took part in the survey. Ten employees were engaged in a face-to-face interview, 2 private and 8 public organisations from among the 40 organisations that participated. Both SPSS and SmartPLS were utilised to analyse data. MGA is used to determine the difference private and public organisations. The study has indicated a significant relationship between employee empowerment and organisational performance. The findings revealed a small but not significant difference between the private and public organisations in their definition of employee empowerment in the Gambia based on MGA report. The findings discovered that the social nature of employees cannot be disputed, and a strong recognition of employees promotes organisation performance. HR department and organisational flexibility relates more to employee’s empowerment and has effect on attitude and behaviour. The study recommends further large-scale research in other environments outside the Gambia.